2021
DOI: 10.52939/ijg.v17i5.2033
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Interaction between Lifestyles and Tuberculosis: An Expert and Public Participatory GIS in Malaysia

Abstract: Human lifestyle factors are potential contributing factors to tuberculosis (TB) transmission in Malaysia, but the previous studies have not comprehensively explored these factors by using geospatial and public perspectives. The aim of the study was to examine the impacts of lifestyle risk factors on TB cases in Shah Alam using an expert and public participatory GIS (PPGIS) approach with the 5-risk scale from 1 to 5. Local health experts have suggested that the overall risk scale of TB-lifestyle factors are 2.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In Malaysia, many researchers have also been exploring the capabilities of GIS-MCDM for disease clustering and pattern analysis (Mohammad et al, 2023;Ridzuan et al, 2021;Zaini et al, 2022;Abdul Rasam et al, 2016). Specifically, the studies suggested that the GIS approach can use to analyze the spatial distribution of disease cluster cases, including to determine the hotspot location of the disease cluster to examine the spatial distribution of the factors affecting the disease cluster.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Malaysia, many researchers have also been exploring the capabilities of GIS-MCDM for disease clustering and pattern analysis (Mohammad et al, 2023;Ridzuan et al, 2021;Zaini et al, 2022;Abdul Rasam et al, 2016). Specifically, the studies suggested that the GIS approach can use to analyze the spatial distribution of disease cluster cases, including to determine the hotspot location of the disease cluster to examine the spatial distribution of the factors affecting the disease cluster.…”
Section: Literature Reviewmentioning
confidence: 99%